The Role of Nurses in Community Awareness and Preventive Health - Marjaneh M. Fooladi (Shiraz University of Medical Sciences, 2015)
With access to multimedia through social networks at global level, one wonders why some of the preventive healthcare services such as children and adult immunizations, annual screening for men and women, prenatal and dental care for childbearing women and adolescents are not provided at a 100% rate. Community awareness is a crucial aspect of preventative healthcare and perhaps those responsible for implementing the national health initiatives seek to realize other key factors influencing community health. In a study of 190 community health nurses caring for blacks, Puerto Ricans and Southeast Asians, the confidence scores for cultural self-efficacy was high when nurses cared for blacks and they were low when they cared for Asians and Latinos. The lowest scores belonged to items related to knowledge of health beliefs and practices regarding respect, authority and modesty within each culture. Scores were higher when interpreters were used correctly to convey meaningful messages. Researchers concluded that nurses lacked confidence when caring for culturally diverse patients and found weaknesses across the nursing curriculum preparing nurses to care for various demographic groups.1 In most countries, including Iran, governmental agencies have the budget and the man- power to apply preplanned initiatives and provide community-based preventive healthcare services to address the majority of the preventable health related issues through satellite clinics, health department and outpatient facilities. Meanwhile, private sectors in metropolitan cities offer cure-based services to urban and suburban communities. Remote and rural areas should be the focus of primary care and preventive health services, because access to multimedia is limited, healthcare providers refuse to work in outreach areas, and unpaved roads are barriers to easy access to the locals and outsiders. To implement an effective community-based preventive program, recognition of resiliency as a theoretical framework within that community should be considered to help explain how communities address adversity.2 In a British study, researchers established the importance of the role of nursing in preventive health when nurses added significant improvement to reduce the major risk factors for cardiovascular disease in middle aged patients. Nurses, compared to other healthcare providers, were able to provide health screening and doubled the recorded blood pressure, quadrupled identification of smoking habit, and increased documented weight related issues by fivefold in a primary care setting.3 Community health nursing theory addresses collective concepts of nursing domains in an attempt to rectify environmental, resiliency, and community abilities for healthcare issues among diverse population and avoids simple groupings of aggregates. Conceptual frameworks are introduced to help urban and rural communities implement preventative measures for health and wellbeing of residents through rural-based community health nursing programs.1,4 With this awareness, Iranian nurses in any practice area will find a golden opportunity to encourage, motivate, inform and guide the public to consider health screening, annual check-ups, childhood and adult immunizations and offer health education to patients across the lifespan. The role of nursing does not begin or end in a hospital-based or clinical facility. It is important to remember "Once a nurse, Always a nurse", which means a nurse can guide and educate the public every minute and in all places, for the mere fact that medicine does NOT. Community health is a major part of nursing profession as Sarah, who graduated from a baccalaureate nursing program 5 years ago, demonstrates her role as a spiritual journey with a firm belief to bring health awareness through motivation. Her usual day begins by telling a 45 year-old male cashier in a supermarket to go for a prostate cancer screening; a 50 year-old woman sitting in the park to have her bone density screening; asking a young mother on the bus if her children are up-to-date with their immunizations; encouraging a 16 year-old adolescent to stop smoking and discuss the adverse effects of nicotine dependency; hold a passionate conversation with a 5 month pregnant woman at a birthday party to consider natural birth versus Cesarean Section and breastfeed; discuss swimming pool safety, poison control, insect bites, falls and motor vehicle accident prevention with a teacher in her neighborhood and so on. Sarah may be unique, but her words are nothing less than the seeds of knowledge planted by a farmer to reap good health. Nurses are the foundation of any successful social healthcare program and instrumental in implementing any private or government funded universal health plan. The role of nurses for improving the health and wellbeing of a society is undeniable and Iranian nurses should take their role more seriously for an everlasting effect on the public wellbeing.